Effects of subsidized crop insurance on crop choices. (30th May 2018) - Yu, Jisang; Sumner, Daniel A.
Abstract: This study focuses on how subsidized crop insurance affects crop choices. Crop insurance may change farm investments by reducing risks and providing subsidies. First, actuarially fair insurance reduces risks in crop production and marketing, holding the expected return constant. Second, insurance subsidies encourage farms to purchase crop insurance, which increases the expected return to insured risky crops. Farms also have many self‐insurance mechanisms such as crop diversification or working off the farm. We derive conditions under which (1) unsubsidized and actuarially fair crop insurance or (2) insurance premium subsidies lead to more investment in a risky higher return crop. We then examine the role of self‐insurance for these conditions. The impact of premium subsidies is decomposed into a direct profit effect and an indirect coverage effect. These effects are explained by substitutions between market insurance and self‐insurance and between a risky crop and a safe crop. We discuss each effect as a combination of subsidy and risk effects. Numerical illustrations show that an insurance subsidy has a larger impact on risky crop investments compared to that of an input subsidy when farms are more risk‐averse and have high costs of self‐insurance. The framework provides a novel way to evaluate subsidized crop insurance programs.